Christianization in Early Medieval Transylvania : a Church Discovered in Alba Iulia and its Interpretations - Mureşan, Dan Ioan, 1974-; Marcu-Istrate, Daniela, 1964-; Rustoiu, Gabriel Tiberiu (East Central and Eastern Europe in the Middle Ages, 450-1450 ;, 2022)
This book takes a multidisciplinary approach to the issue of the Christianization of Transylvania, starting from the recent archaeological discovery of a 10th-century, Byzantine-style church in Alba Iulia.